Establishment of Assertive Attitude: Effort to Overcome Juvenile Delinquency - Sandi, Fadia Aulia; Faturrochman, Aydin Farrelyno; Rizkhianzah, Muhammad Akbar (International Conference on Psychology and Education (ICPE), 2025)
The purpose of this study was to minimise juvenile delinquency through the formation of a good assertive attitude. In addition, it provides views on the importance of applying assertiveness, especially for adolescents. The research method used is a descriptive analysis literature study carried out by collecting data from various literature sources such as books, journals, and other data sources. The purpose of this literature study is to develop theoretical and practical aspects in a research topic. Descriptive methods are used to describe or explain phenomena or objects of study in detail and systematically. From the results of descriptive analysis, it was found that assertive attitudes correlated negatively with juvenile delinquency. Which means when someone has high assertivity, the number of juvenile delinquencies will be low.